Impact of recurrent hospitalization for Clostridioides difficile on longitudinal outcomes in patients with inflammatory bowel diseases: a nationally representative cohort. (December 2022) - Venkat, Preethi G.; Nguyen, Nghia H.; Luo, Jiyu; Qian, Alexander S.; Khanna, Sahil; Singh, Siddharth
Background: Clostridioides difficile infection (CDI) is associated with poor outcomes in patients with inflammatory bowel diseases (IBD). Objectives: We conducted a nationally representative cohort study to evaluate the impact of recurrent CDI (rCDI)-related hospitalization on longitudinal unplanned healthcare utilization in patients with IBD. Design: This was a retrospective cohort study that utilized the 2017 Nationwide Readmissions Database (NRD). Methods: We identified 13, 446 patients with IBD, hospitalized at least twice from January to June 2017 and followed through December 2017; of these, 1, 148 had CDI-related hospitalizations. We compared the annual burden of hospitalization and IBD-related surgery in IBD patients with rCDI-related admission versus single CDI-related admission (primary reference), and those with one or more CDI-related admission versus no CDI-related admission (secondary reference). Results: There were no significant differences in risk and burden of unplanned healthcare utilization (time spent in-hospital, 27 days versus 27 days, p = 0.62), 6-month readmission (63% versus 64.3%, p = 0.8) or IBD-related surgery in patients with recurrent (two or more) CDI-related hospitalizations versus single CDI-related admission. However, patients with ⩾1 CDI-related admission versus no CDI admissions experienced higher rate of 6-month readmission (61.1% versus 55.7%, p <.001), total days spent in the hospital per year (median: 26 days versus 21 days, p <.001), total cost across all hospitalizations per year (212, 524 versus 184, 384, p < 0.01), and inpatient mortality (3.28% versus 1.81%, p = 0.01), without an increase in risk of IBD-related surgery (6.7% versus 6.4%, p = 0.79). Conclusion: While patients with IBD hospitalized for CDI have poor longitudinal inpatient outcomes, recurrent admissions for CDI may not increase risk of adverse outcomes compared to one-time admission.